African cinema on demand? The politics of online distribution and the case of the African Film Library. (1st September 2018) - Fisher, Alexander
This article considers the impact of online distribution on the long-term availability and preservation of African cinema. It examines the case of Electronic Media Network's (M-Net) African Film Library (AFL), a video-on-demand (VOD) library of classic African films that was launched in 2012, but taken offline by 2013. The article argues that this short-lived project represents a pivotal moment in the way we think about African film archiving and distribution, in which new technologies and consequently disintermediated business models promised to facilitate the circulation of African films in a manner that was socially beneficial, but which in reality resulted in monopolistic control of the content that presented a serious threat to its long-term preservation. The article goes on to argue that the AFL case encapsulates the entire discourse surrounding the shift to online distribution, in which a 'cybertopian' narrative of a disintermediated and thus democratized film culture quickly gives way to a reality in which content is more tightly controlled by an increasingly narrow and powerful set of private stakeholders, ultimately threatening the preservation of any content that is vulnerable to the shifting demands of the market.